2022
DOI: 10.1038/s41597-022-01849-7
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years of volcano geodesy from space at Campi Flegrei caldera (Italy)

Abstract: This work provides the mean ground deformation rates and ground displacement time series of the Campi Flegrei caldera (Italy) retrieved by satellite remote sensing data analysis from 1992 to 2021. Synthetic Aperture Radar (SAR) images acquired by ERS 1–2 (1992–2002), Envisat (2003–2011) and Cosmo-SkyMed (2011–2021) are processed by multi-temporal SAR Interferometry (InSAR) approach using the same technique, parameters and reference system, to obtain for the first time a homogeneous and time-continuous dataset.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Although there is no evidence of spatial variation in the primary deformation source inferred from GPS data analysis (De Martino et al., 2021), changes in the deformation rate since 2012 have been recently observed (see, e.g., Tripaldi et al., 2022). This change of the Phlegrean deformation field is also confirmed by the InSAR measurements carried out in the area, compared with the measurements provided by precise leveling lines and cGNSS stations belonging to the Neapolitan Volcanoes (Polcari et al., 2022).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although there is no evidence of spatial variation in the primary deformation source inferred from GPS data analysis (De Martino et al., 2021), changes in the deformation rate since 2012 have been recently observed (see, e.g., Tripaldi et al., 2022). This change of the Phlegrean deformation field is also confirmed by the InSAR measurements carried out in the area, compared with the measurements provided by precise leveling lines and cGNSS stations belonging to the Neapolitan Volcanoes (Polcari et al., 2022).…”
Section: Discussionsupporting
confidence: 71%
“…Significant ground deformation resulting in more than 150 cm of vertical uplift occurred during the crisis of 1982–1984. Since the last months of 2005, a new unrest started with an increasing rate of uplift (De Martino et al., 2021; Polcari et al., 2022) (about 90 cm up to now), seismicity (Bellucci Sessa et al., 2021), and degassing activity (Cusano et al., 2021). Uplifts are related to both magmatic and hydrothermal sources (Cannatelli et al., 2020; Lima et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…During the selection of the case studies, attention was also paid to the underlying mechanism resulting in the observed ground surface deformation. Campi Flegrei is subject to volcanic activity, alternating phases of inflation and deflation [48,49]. The Volturno Coastal River Basin is affected by both naturally occurring processes, i.e., the consolidation of fluvial and palustrine deposits, and human activity in the form of water exploration and urbanization [50].…”
Section: Discussionmentioning
confidence: 99%
“…The region of Campi Flegrei is a densely populated area affected by volcanic activity, alternating phases of inflation and deflation [48,49]. The associated ground surface deformation can be observed over an area of roughly 224.9 km 2 .…”
Section: Demonstration Casesmentioning
confidence: 99%
See 1 more Smart Citation